Phylogeny of Phlegmariurus (Lycopodiaceae) focusing on Brazilian endemic species - Gissi, Danilo Soares (2017)
Phlegmariurus is the most abundant genus of Lycopodiaceae in Brazil with 40 species, 24 of which are endemic, occurring mainly in the Atlantic Rainforest and Rocky Fields (“Campos Rupestres”) in the Espinhaço range. Some phylogeny works with the group had already been carried out, but not including a representative sample of the Brazilian species. Thus, we performed a molecular phylogeny of Phlegmariurus species endemic in Brazil using three molecular markers of cpDNA. Phlegmariurus showed to be monophyletic, including two clades, one Neotropical and another Paleotropical. All the Brazilian species sampled appeared in the Neotropical clade. The endemic species appeared in several clades alongside Andean species. Epiphytism and the microphylls differentiation were optimized at the obtained clade and they appeared several times in the evolutionary history of the group